Streaming in swarm of UAVs and MEC assisted networks - Bari, Rahil; Bousbaa, Fatima Zahra; Lagraa, Nasreddine (Université Amar Telidji - Laghouat - Département d'informatique, 2022)
With the continuing advancements in smart computation and communication technologies in the recent past, Unmanned Aerial Vehicles (UAVs) and Mobile Edge Computing (MEC) play an important role in the Internet of Things (IoT) as intelligent objects, and they may become an interesting way to oﬀer new IoT services when they are equipped with suitable IoT devices. The majority of IoT real-time applications such as, video streaming services, agriculture surveillance and medicine applications require high amount of resources and IoT devices that cannot be oﬀered by a single Unmanned Aerial Vehicle (UAV), Therefore, a single IoT service may require the involvement of swarm of cooperatives UAVs. In this work, streaming with routing problem in swarm of UAVs and MEC servers will be studied, which aims at delivering information to specifc members of mobile drones. The objectives of this work are to (1) provide detailed classifcation of existing streaming swarm protocols considering transmission strategies and to (2) propose a new streaming technique aiming to reduce the End-to-End delay of UAVs and efciently explore networks and searching 3D routing paths with higher network throughput. The results of the simulation conducted using Omnet++ simulator advocate for the efciency of our method through two proposed versions (using AODV and DSDV routing protocols) in term of reducing the End-to-End delay and increasing throughput.